On stochastic equations - Surgailis, D. (Lithuanian Mathematical Journal, 1969)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:Д. Сургайлис. О стохастических уравненияхD. Surgailis. Apie stochastines lygtis